Theoretical Insight into High‐Efficiency Triple‐Junction Tandem Solar Cells via the Band Engineering of Antimony Chalcogenides. Issue 4 (26th February 2021) - Cao, Yu; Liu, Chaoying; Jiang, Jiahao; Zhu, Xinyun; Zhou, Jing; Ni, Jian; Zhang, Jianjun; Pang, Jinbo; Rummeli, Mark H.; Zhou, Weijia; Liu, Hong; Cuniberti, Gianaurelio
Abstract : Antimony chalcogenides have become a family of promising photoelectric materials for high‐efficiency solar cells. To date, single‐junction solar cells based on individual antimony selenide or sulfide are dominant and show limited photoelectric conversion efficiency. Therefore, great gaps remain for the multiple junction solar cells. Herein, triple‐junction antimony chalcogenides‐based solar cells are designed and optimized with a theoretical efficiency of 32.98% through band engineering strategies with Sb2 S3 /Sb2 (S0.7 Se0.3 )3 /Sb2 Se3 stacking. The optimum Se content of the mid‐cell should be maintained low, i.e., 30% for achieving a low defect density in an absorber layer. Therefore, Sb2 (S0.7 Se0.3 )3 ‐based mid solar cells have contributed to elevate the external quantum efficiency in triple‐junction devices by the full utilization of the solar spectrum. In a single‐junction solar cell, the bandgap gradient is regulated through the Se content gradient along the depth profile of Sb2 (S1− x Se x )3 . Besides, an increasing Se content profile provides an additional built‐in electric field for boosting hole charge carrier collection. Thus, the high charge carrier generation rate leads to a 17.96% improvement in the conversion efficiency compared with a conventional cell. This work may pave the way to boost the conversion efficiency of antimony chalcogenides‐based solar cells to their theoretical limits. Abstract : Antimony chalcogenides‐based triple‐junction tandem solar cells can achieve a theoretical efficiency of 32.98%. Herein, Sb2 S3 /Sb2 (S0.7 Se0.3 )3 /Sb2 Se3 tandem solar cells have been theoretically simulated by tuning their thickness and compound stoichiometry. Besides, Sb2 (S1− x Se x )3 single‐junction solar cells with an increasing Se content profile could promote the incident light absorption and the hole transport, which leads to a higher efficiency of 15.50%.